Contradições da formação humana e profissional no curso de direito: uma aproximação com base nas representações de estudantes de três universidades particulares de São Paulo - Ferreira, Antonio Carlos Gomes (2022)
This thesis aims to analyze why young people choose a legal career in current society and what justifies their ideological option in the understanding of legal theory and practice. Considering a traditional teaching, based on fragmented knowledge, characteristic of the capitalist system under the neoliberalism paradigm, it sought to understand and evaluate the presence of humanistic training/formation in Law courses and its benefits for the life projects of the students. To this purpose, an analysis is developed based on the representations of law students from three private universities in the city of São Paulo, collected through responses to a specific questionnaire. After a historical review of the trajectory of Law courses in Brazil, through bibliographic and documentary analysis, to characterize their tradition in our cultural context, the questionnaire was applied to the students, divided into three groups: students graduating from high school, beginners, and graduating students of the Law Course, seeking to demonstrate, respectively, the projected expectations, the initial perception and the evaluation of the training/formation received. Based on the epistemological framework of dialectical materialism, the research confirmed the hypothesis that legal training/formation, in the investigated Universities, occurs in a fragmented and ideologized epistemological way, even though, theoretically, the formal documents and referenced pedagogical paradigms claim that there is a humanistic training in these Law Courses. In the end, this thesis recommends the configuration of a formative proposal for the Law course effectively committed to the emancipatory objectives of the legal field. Considering that, in the face of a global society permeated by crises, injustices and social inequalities, it is essential to search for new educational references in a perspective of human formation of legal people, making it increasingly necessary to curriculum aimed at the humanistic Law teaching.